2018
DOI: 10.18775/ijied.1849-7551-7020.2015.41.2001
|View full text |Cite
|
Sign up to set email alerts
|

Research on Relationship between Financial Inclusion and Economic Growth of Rwanda: Evidence from Commercial Banks with ARDL Approach

Abstract: This study examines the relationship between financial inclusion and economic growth of Rwanda using annual data from 2004 to 2016. We used ARDL as it is a new approach to the problem of testing the existence of a level relationship between a dependent variable and a set of regressors, when it is not known with certainty whether the underlying regressors are trend-or first-difference stationary as developed by Pesaran. The results of our study revealed that there is long-run relationship between financial incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…They observed positive impacts of insurance market penetration on economic growth of the sample countries. Employing data for the period of 2004 to 2016, Bigirimana and Hongyi (2018) found that financial inclusion through commercial banks has major long-run effects on Rwanda's economic growth. Kim et al (2018) employed the data of 55 OIC countries from 1990 to 2013 and found significant contributory effects of financial inclusion on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They observed positive impacts of insurance market penetration on economic growth of the sample countries. Employing data for the period of 2004 to 2016, Bigirimana and Hongyi (2018) found that financial inclusion through commercial banks has major long-run effects on Rwanda's economic growth. Kim et al (2018) employed the data of 55 OIC countries from 1990 to 2013 and found significant contributory effects of financial inclusion on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using the Financial Global Findex dataset, a number of academics formulated a thorough multidimensional computation of FI. Bigirimana and Hongyi [20], Mehrotra and Yetman [21], Ali, et al [12], Ratnawati [13], Neaime, et al [14], Sarma [22], Verhoef and Hidden [15], Morgan [5], Kim [2], Dogan, et al [6], Park and Mercado [16], Ratnawati [17], Sahay, et al [1], Beck, et al [23], Polloni-Silva, et al [8], and Erlando, et al [9], among others, are the most famous authors in this category of works. These academics created multidimensional and composite indexes of FI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employing ASEAN countries’ data over the period of 1988–2012, authors found that insurance market penetration caused economic growth of the countries. Bigirimana and Hongyi (2018) conducted a study on the impacts of financial inclusion through commercial banks on economic growth of Rwanda. Using the data of 2004–2016, authors found that financial inclusion had significant long-run impacts on the economic growth of Rwanda.…”
Section: Literature Reviewmentioning
confidence: 99%